MyotonPRO is a Reliable and Repeatable Tool for Measuring Mechanical Properties of the Upper Limb Muscles in Patients with Chronic Stroke - Taş, Serkan; Aktaş, Arda; Tufek, M. Taha; Dağ, Figen (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2022)
Background/Aim Muscle mechanical properties can be measured using a variety of methods. The current study intended to examine the inter-session and inter-rater reliability of the MyotonPRO for assessing the mechanical properties of the upper limb muscles in chronic stroke patients.Materials and Methods The research included 20 stroke patients (14 male and 6 female) ranging in age between 36 and 84 years (65.1±11.2 years). A MyotonPRO was used to assess the oscillation frequency, stiffness, and logarithmic decrement of the triceps brachii, biceps brachii, upper trapezius, and deltoid muscles. Two physiotherapists conducted the assessments to determine the tool's inter-rater reliability. A physiotherapist repeated the measurements 3 days after the first measurements for determining the inter-session reliability of the tool.Results The ICCs of all assessed muscles ranged within 0.72–0.97. The coefficient of variation of all muscles varied within 3.2–11.0%, 3.4–9.7% for oscillation frequency, 3.9–7.4% for stiffness, and 3.2–11.0% for decrement. In the measured muscles, the standard error of assessment varied within 0.5–1.2 Hz for frequency, 9.2–21.2 N/m for stiffness, and 0.1–0.4 for decrement.Conclusions The results indicate that MyotonPRO has a between good and excellent inter-section and inter-rater reliability for measuring the tone, stiffness, and elasticity of the triceps brachii, biceps brachii, upper trapezius, and deltoid muscles in chronic stroke patients. MyotonPRO can be used for the diagnostic and therapeutic intention in chronic stroke patients.
Keywords: Myotonometry; reliability; stroke; muscle stiffness; muscle tone; muscle elasticity